Tropospheric aerosol - formation, transformation, fate and impacts: University of Leeds, United Kingdom, 22 - 24 July 2013 ; [a General Discussion on Tropospheric Aerosol - Formation, Transformation, Fate and Impacts] - McFiggans, Gordon (Faraday discussions, 2013)
A general discussion on "Tropospheric aerosol: formation, transformation, fate and impacts" was held in Leeds, UK on 22nd, 23rd and 24th July 2013. It was co-sponsored by the Aerosol Society
Includes bibliographical reference and author index
Keywords: Konferenzschrift; Aerosol; Troposphäre